PENGARUH GOOD CORPORATE GOVERNANCE, KUALITAS AUDIT & LEVERAGE TERHADAP MANAJEMEN LABA PADA PERUSAHAAN JASA SEKTOR PARIWISATA YANG LISTING DI BEI PADA 2012-2015 - rizka indri arfianti (Jurnal Ekonomi Perusahaan, 2017)
Various accounting manipulation case involving several multinational and national company, such as Enron, WorldCom, Kimia Farma, and Lippo Bank has been panicked economic actors and investors. Various practic of earning management oftenly found in several companies. Based on this reason, mechanism of good corporate governance and audit quality’s reliability have been questioned. This research aims to know the influence of good corporate governance mechanism measured by institutional ownership, independent audit committee, and management ownership also audit quality and leverage toward earning management by discretionary accrual. Agency theory is being the basis of earning management practic in company. Differences of interest between management and shareholders being a root of pressure for management to do earning management. Inconsistency revenue also being a strong reason for management to do earning management.This research sample consisted of 54 tourism sector service companies listed in BEI during 2012-2015. Samples obtained by using purposive sampling method. Data analytical technique used in this research are classical assumption test and multiple linear regression with the help of SPSS version 21. Based on the result of multiple linear regression analysis showed that institutional ownership has significance value of 0,2905.  Independent audit committee has significance value of 0,061. Management ownership has significance value of 0,0005. Otherwise, audit quality and leverage has significance value of 0,3225 and 0,163. Analytical result of this research shows us that institutional ownership and independent audit committee doesn’t have an sufficient influence evidence towards earning management. This is in accordance with audit quality and leverage that doesn’t have an sufficient influence evidence towards earning management. Otherwise, management ownership has a significant influence towards earning management.